REPORT ON SOCIO-ECONOMIC IMPACT OF COVID 19 ON MIGRANT WORKERS WITH REFERENCE TO KERALA STATE - P. M, Sreejith; S. , Sreejith (The journal of contemporary issues in business and government, 2021)
Kerala is one of India's main destination regions for immigrants, and migrants make up a large percentage of Kerala's workforce. Migrant workers all seem to be in all occupations and sectors of the regional economy because of high pay levels and growing demand for manual labor jobs. Immigrants and their children have been attracting tea and coffee plantations, construction, tourism and the hotel industry from other states in the region. Unqualified immigrants in this state can be narrowly defined as those employed on a contract basis, under a contractor or agent for a fixed period, and those employed on a day-to-day basis as regular wagers finding jobs in the labor market. Centered on the data collected via the survey method in Kerala's districts, this research aims to explore the social effect of lockdown. The sampling evidence indicates that the whole population, except the government employees, has suffered the brunt within terms of declining well-being. Self-employed people, too, have been able to boost their family stability significantly.” The article also aimed to investigate and analyze the response of state policy to the crisis. The Kerala government's efforts, to tackle the pandemic show that they have been creative and exceptional. Even then, it is unlikely that reductions in the state's tax and non-tax revenue would sustain and retain these measures. Many of these migrants are compelled to take their families with them to their place of relocation, without as much social or community commitments to take care of their families while they are far gone. They are regarded as outcasts and are neither valued nor equally viewed as an integral part of their destination's community. Many immigrants are illiterate and ignorant, belong to disadvantaged communities and are mainly active in the informal or unorganized field. During regular and overtime work, they are abused, prejudiced by the payment of salaries and other benefits, the allocation of jobs, and employment terms. They are not coordinated, and they do not secure their labor standards.”